PHYSICAL AND CHEMICAL PROPERTIES OF LOCAL HONEY FROM EAST KALIMANTAN - Umul Karimah; Rika Melati; Ayu Anita Sari Ratna Saputri (Jurnal Penelitian Hasil Hutan, 2020)
Most of the local honey production in East Kalimantan is managed traditionally, thus honey quality, particularly its physical and chemical properties, are unknown. However, the honey analysis provides a comprehensive composition profile and potentially gives hints to improve the quality of local honey from East Kalimantan. This research aimed to analyse the properties of two local honey from East Kalimantan. The methods used in this study were gravimetric, volumetric, spectroscopy, spectrophotometry, and chromatography. Honey A was produced by Apis cerana whereas Apis dorsata produced honey B. The color intensities were 560±5.66 and 947.5±27.58 mAu for honey A and B, respectively. Honey A and B a had moisture content of 22.7 and 25.8% w/w, respectively. Other proximate analysis parameters were also reported. Fructose and glucose content for honey A were 30.65±2.35% w/w and 30.08±0.58% w/w, while honey B gave different pattern with fructose at 28.06±1.04 and higher glucose instead at 32.74±1.13% w/w. Reducing sugar and total sugar for both samples were higher than 60% w/w while sucrose in honey A and B were 2.8 and 1.4% w/w respectively, thus indicating no adulteration. Vitamin C content measurement showed negligible result with total phenolic content of honey A was lower than honey B. Honey B had higher Na, Ca, Fe and Zn than those of honey A. This study reported thorough chemical composition of local honeys from East Kalimantan in which some could have significant nutritional value. However, quality improvement particularly on moisture and reducing sugar content is necessary to meet Indonesian National Standard 8664:2018.